Calidad del agua y salud pública en el Istmo Centroamericano - Donato, Carlos (1976)
As of December 1970 the population of the Central American Isthmus was 16,436,723; 6,225,447 (37.9%) urban and 10,210,946 (62.1 %) rural. Of the urban population, 63.3%, or 3,941,611 had water in the home, while 2,283,836 (36.7%) had no adequate water supply. The problem is even worse in the rural population where only 732,150 inhabitants (7.17%) had water in the home; the rest, 9,500,000 were using water from contaminated rivers, streams, wells, etc.These low percentages do not meet the standards proposed at Punta del Este, Uruguay in 1961 of providing drinking water to 70% of the urban population and to 50% of those of rural areas. Nor do the very low figures for sanitary disposal of wastes meet these standards (31.4% in urban areas and 19.5% in rural areas). As a logical consequence, water-bourne morbility in the Central American Isthmus is very high. The rates per 100,000 inhabitants are 0.4 to 18.8 for typhoid fever; 0.7 to 13.0 for paratyphoid fever; 0.5 to 786.2 for bacillary dysentery; and 17.9 to 555.6 for amebiasis.Although it would be hard to evaluate the benefits of sanitary water and waste disposal systems, the damage caused by water-bourne illnesses is well known, especially their effect on the individual human being since they sap his energy, lower his life expectancy and productivity, and thus indirectly affect the national economy. It is a well known fact that the cost of optimum water supply and waste disposal systems will more than amply be paid for by the savings in medication and lost time through illness.